FACTORS AFFECTING CAREER CHOICE OF STUDENTS IN SECONDARY SCHOOL: A REVIEW - Namera, Mohammed Aishat; Namera, Balkisu Mohammed (Sokoto Educational Review, 2020)
This paper takes a look at the factors affecting-career choice of students in secondary schools, hence schools is a significant agent of socialization where individuals acquire various attitudes, knowledge and skills which eventually influence career choice. The writer discussed on how students accidentally choose career without proper guidance and counseling. The factors affecting career choice of student. The paper concludes with how career must be carefully chosen, well planned, organized, implemented and evaluated. With these review, it is recommended that functional guidance and counseling units should be established in all secondary schools and tertiary institutions to help students in career guidance.